The “Fuyuzat” Journal as an Effort to Forma Common Turkic Language at the Beginning of The 20th Century - Azizova, Elnura (Scholarya Demo Journal of Ruby, 2019)
The events that occurred at the beginning of the 20th century in Russia's international and national policy affected the future of Azerbaijani Turks like other nations living within the territory of the Tsarist Russia. Newspapers and journals in Azerbaijani Turkic language like “Hayat” (1905-1906), “Teze Hayat”(1907-1908), “Terakki”(1909), “Burhan-i Terakki”, (1906-1911), “Rehber”(1906-1907), “Debistan” (1906-1908), “Behlul”(1907), “Lek-lek”(1914) began to operate consecutively after 1905. Among these publications “Molla Nasreddin”(1906-1931) published in Tbilisi, Baku, and Tabriz and “Fuyuzat”(1906-1907) published only in Baku, were the two well-known andpopular periodicals with huge impact on the society.  The Fuyuzat was published under the sponsorship of Zeynelabidin Tagiyev, the prominent businessman, benefactor and the philanthropist of Azerbaijan in the fields of oil industry, education and culture. The chief editor of the Füyuzat Ali Bey Hüseynzade, as well as the other columnists of the journal either studiedor lived in Istanbul. So, the journal provided information not only for Azerbaijani Turks, but also Turks living in Russia about political, social and cultural eventssurrounding the Ottoman Empire at the beginning of the 20th century. One of theprincipal goals of the journal was to establish a unified common literary Turkic language among Turks. Through disseminating information among Turkic nations the journal aimed at achieving this goal as well. The journal pursued the policy of Turkification as an alternative to the Russification of the Russian Czarist through making an effort to create an identity based on national sense. In this sense, the Fuyuzat played a central rolein the formation of national identity in Azerbaijan at the beginning of the 20th century. However, the journal had received various criticisms about itslanguage from the written press in Azerbaijan during its period of publicationand afterwards. The rationale behind the criticism was that the Ottoman language, as the synthesis of Arabic, Persian and Turkish addressed to the educated layer of the society. So, it was argued that the Fuyuzat was not as influential as the journal Molla Nasreddin that was published under the editorship of  Jalil Mammadguluzadeh who famously said for the language ofhis publication “in the pure mother tongue of the Turk”.  The aim of this article is to investigate the role of the Füyuzat in the formation the literary Turkish language in Azerbaijan at the beginning of the 20th century. Through studying the journal’s articles, we assess and analyze the criticism of the journal’s attempt to establish a unified Turkish language.